“Diabetic foot” in Oman: A systematic review and COM-B public health intervention framework - Saud Al Harthi; Thamra Al Ghafri; Nahal Afifi; Aisha Al Mehrazi (International Journal of Public Health Science (IJPHS), 2026)
Diabetic foot disease (DFD) is a preventable but rapidly growing complication of diabetes in Oman. The individual and societal consequences of DFD are catastrophic; however, best practices in its management remain underreported. This review aimed to identify, appraise, and synthesize the available evidence on DFD in Oman and to map findings onto the capability, opportunity, motivation, behaviour (COM-B) model to guide public health interventions. Five databases (PubMed, Scopus, Cochrane Library, WHO EMRO repository, Google Scholar) and two Omani journal archives were searched from inception to March 2026. Records were screened independently by two reviewers, and methodological quality was appraised using an adapted Newcastle-Ottawa scale. Findings were mapped deductively onto the six COM-B sub-domains and to the behaviour change wheel intervention functions. Ten publications met inclusion criteria. Diabetes related lower limb amputations account for 47% of all amputations nationally. Concurrent deficits were found across capability (55% lacked knowledge of DFD causes), opportunity (no multidisciplinary foot teams outside Muscat; 50 to 54% barefoot walking), and motivation (38% performed regular foot examination). Limitations include lack of interventional studies, urban concentration, and self-reported outcomes. Policy priorities are a national DFD registry, multidisciplinary foot care beyond Muscat, and integration of behaviour change techniques into primary care.